THE DESCRIPTION OF EXCLUSIVE BREASTFEEDING AS LACTATION AMENORRHEA METHOD CONTRACEPTION) - Desy Jein Rimelda Masombe; Risa Etika; Bambang Purwanto (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground: Exclusive breastfeeding has benefits as a natural contraceptive method, the Lactational Amenorrhea Method (LAM). The coverage of exclusive breastfeeding in East Java Province in 2018 only reached 74.3% and coverage of active family planning was still at 75.3% (Health Office of East Java, 2018). The results of a preliminary study of 10 Children’s Health Specialist Doctor Education Program of Airlangga University showed exclusive breastfeeding, but only 20% managed to menstruate for more than 6 months. This study aims to determine the description of exclusive breastfeeding as LAM at Dr Soetomo Hospital Surabaya. Method: This type of research uses a descriptive method to mix method research with survey analytic methods. The number of samples used was 16 people with simple random sampling technique. Results: PPDS who got LAM success during exclusive breastfeeding, by giving on demand and frequency more than 8 times was only 37.5%, while the remaining 62.5% PPDS failed to achieve LAM. The inhibiting factors are not being able to give immediately, time for pumping, and inadequate rest. The support received by PPDS is tolerance for pumping, high determination of exclusive breastfeeding, and family support. How to give breast milk is to breastfeed directly and by bottle. The reason for using the bottle is to work. The number of PPDS with amenorrhea duration 1-3 months was 7 people, and only 1 PPDS experienced amenorrhea for 12 months. Conclusion: Nearly half of PPDS have successfully used LAM as a contraceptive.